On Legal Practice and Other Criteria for the Truth of Knowledge about the State and Law - Vladimir Valentinovich Kozhevnikov (Budapest International Research and Critics University, 2022)
This scientific article analyzes various criteria for the truth of knowledge about the state and law. The work emphasizes a very important and fundamental position, according to which legal practice, being the most important criterion for knowledge about the state and law, cannot objectively be recognized as a single criterion, because far from all knowledge about many state-legal phenomena and processes cannot be "measured", based solely on legal practice.